Dazed, Confused, and Asystolic: Possible Signs of Anti–N-Methyl-D-Aspartate Receptor Encephalitis - Ziaeian, Boback (Tex Heart Inst J, 2015)
Anti–N-methyl-D-aspartate (NMDA) receptor encephalitis is a rare panencephalitis that can present with severe cardiac dysrhythmias. We present a case of a 19-year-old woman with no significant medical history who presented with progressive changes in mental status and profound ictal asystole that necessitated the placement of an external temporary pacemaker. She was diagnosed with and treated for anti-NMDA receptor encephalitis, and she recovered after a prolonged and complicated hospitalization. We review the pathophysiology and management of anti-NMDA receptor encephalitis, as well as its cardiac manifestations.